Financial Behavior and Risk Tolerance as Determinants of Investment Decision Making among Young Adults in Urban Areas - Rizky, Ahmad; Wulandari, Lestari; Azizah, Nurul; Walsh, Fiona (Journal of Economics and Management, 2025)
This study investigates the relationship between financial behavior, risk tolerance, and investment decision-making among young adults in urban Indonesia. Using a quantitative approach, primary data were collected from 250 respondents aged 20–35 years residing in five major urban centers through an online survey. The study employs Structural Equation Modeling–Partial Least Squares (SEM–PLS) to analyze the interrelationships among financial literacy, budgeting habits, saving behavior, risk tolerance, and investment decision quality. The findings reveal that financial behavior significantly affects investment decision-making, both directly and indirectly through the mediating effect of risk tolerance. Respondents with disciplined saving and budgeting habits exhibit higher risk tolerance and tend to make more rational and goal-oriented investment choices. The study highlights the need for targeted financial education programs that address behavioral factors and risk profiling in order to improve the quality of investment decisions among urban youth.